2021
DOI: 10.14701/ahbps.2021.25.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Robotic major liver resections: Surgical outcomes compared with open major liver resections

Abstract: Backgrounds/Aims: Laparoscopic major liver resections are still considered innovative procedures despite the recent development of laparoscopic liver surgery. Robotic surgery has been introduced as an innovative system for laparoscopic surgery. In this study, we investigated surgical outcomes after major liver resections using robotic systems. Methods: From January 2009 to October 2018, 70 patients underwent robotic major liver resections, which included conventional major liver resections and right sectionect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 32 publications
3
19
1
Order By: Relevance
“…All reviewers approved of the final set of included studies. In total, 11 studies reported data on 146 patients undergoing robotic surgery for cholangiocarcinoma (CC) [ 5 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ], and 10 studies reported data on 113 patients undergoing robotic surgery for gallbladder cancer (GBC) [ 6 , 15 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All reviewers approved of the final set of included studies. In total, 11 studies reported data on 146 patients undergoing robotic surgery for cholangiocarcinoma (CC) [ 5 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ], and 10 studies reported data on 113 patients undergoing robotic surgery for gallbladder cancer (GBC) [ 6 , 15 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Yang et al compared 70 robotic liver resections (only 6 of which included CC) to 252 open liver resections. They reported longer operative time with the robotic approach, but shorter length of stay and lower blood loss [ 12 ]. Xu et al is the only study comparing the robotic ( n = 10) and open ( n = 32) approach strictly in patients with CC.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, laparoscopic robotic surgery, with its greater flexibility, can overcome the limitations of laparoscopic surgery alone and improve surgical accuracy. Furthermore, compared with open surgery, robotic surgery can shorten the length of hospital stay and reduce postoperative complications (23). However, prospective and randomized controlled studies comparing LH and OH have not been carried out.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of short- and long-term outcomes of 70 patients who underwent robot-assisted hepatic resections with a group of 252 patients who underwent open hepatic resections was reported [ 72 ]. Operative time was longer in the robot-assisted group (472 min vs. 349 min, p < 0.001), and estimated blood loss was lower in the robot-assisted group (269 mL vs. 548 mL, p = 0.009).…”
Section: Comparative Studiesmentioning
confidence: 99%